Konteksty regionalne i tożsamościowe w tekstach piosenek śląskich raperów - Stępień, Patryk (Studia Edukacyjne, 2022)
The article is devoted to identify the regional and identity contexts in the lyrics of songs by Silesian rappers. The selection of artists was based on two criteria: they were born or raised in Silesian district and they still live there and the second is the most popular (as an Silesian rapper) by listeners on Spotify.com in June 2022. Rap is a unique kind of music with a lot of listeners. Rap as a part of popular culture would be useful in education as an example of sharing regional values, mentality, desirable behaviors, and the position of the Silesian identity in their lives. The lyrics contain the artists’ points of view on reality, the living conditions, and probably include guidance for listeners. Silesian rappers and their experience of being Silesian and a sense of Silesian identity could be part of the lyrics.